Bacterial inactivation by a carbon nanotube–iron oxide nanocomposite: a mechanistic study using E. coli mutants. Issue 2 (20th December 2017) - Engel, Maya; Hadar, Yitzhak; Belkin, Shimshon; Lu, Xinglin; Elimelech, Menachem; Chefetz, Benny
Abstract : Inactivation of E. coli by the carbon nanotube–iron oxide nanocomposite. Abstract : Waterborne pathogens are a major health threat and must be eliminated to guarantee safe usage of water for potable purposes. For this purpose, a new carbon-based nanomaterial composed of single-walled carbon nanotubes (SWCNTs) and iron oxides was constructed for bacterial inactivation. Owing to its magnetic properties, the SWCNT–iron oxide nanocomposite may serve as a reusable antimicrobial agent. The nanocomposite material exhibited high antimicrobial activity against Escherichia coli . Successful reuse of the nanocomposite material was achieved by washing with calcium chloride and distilled water, which restored its performance for several successive cycles. To investigate the cytotoxicity mechanisms of the nanocomposite material, we exposed it to single-gene knockout mutant strains of E. coli . Mutants bearing shorter lipopolysaccharide (LPS) layers in the outer membrane (Δ rfaC and Δ rfaG ) demonstrated an increased sensitivity in comparison to the wildtype strain, exemplified in enhanced removal by the nanocomposite material. This finding suggests that the LPS acts as a protective shield against the nanocomposite material. Inactivation of mutants impaired in specific oxidative stress defense mechanisms (Δ sodA, Δ katG and Δ soxS ) emphasized that oxidative stress plays a significant role in the inactivation mechanism of the nanocomposite. This study sheds light on the mechanisms of bacterial inactivation by carbon-based nanomaterials and advances their potential implementation for water disinfection.